2018
DOI: 10.1108/jefas-03-2017-0053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of institutional quality and the development of the banking system on corporate debt

Abstract: Purpose This study aims to determine if the quality of national institutions and banking development condition the maturity of debt depending on the horizon of short or long term. Design/methodology/approach Analysis is performed on a sample of 116 nonfinancial companies from Peru and Brazil. The measures of quality of national institutions and banking development were obtained from World Bank data and included factorial analysis for dynamic considerations. Findings The findings, through the treatment of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…These method has been used by the majority of studies listed in our literature review above, e.g. Chiuri et al (2002), Francis and Osborne (2012), Karmakar and Mok (2015), Aiyar et al (2016), Ben Naceur et al (2018), Tresierra and Reyes (2018), El Hourani and Mondello (2019), and van Duuren et al (2020). Note that the Fixed Effects method allows taking into consideration the bank-specific effects in the estimations by including individual intercepts for each cross-section.…”
Section: Methodology and Variables Specificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These method has been used by the majority of studies listed in our literature review above, e.g. Chiuri et al (2002), Francis and Osborne (2012), Karmakar and Mok (2015), Aiyar et al (2016), Ben Naceur et al (2018), Tresierra and Reyes (2018), El Hourani and Mondello (2019), and van Duuren et al (2020). Note that the Fixed Effects method allows taking into consideration the bank-specific effects in the estimations by including individual intercepts for each cross-section.…”
Section: Methodology and Variables Specificationsmentioning
confidence: 99%
“…Particularly, the author found that economic freedom is a major determinant of bank credit flows in all countries regardless of the level of their economic development and a higher economic freedom results in an increase in credit flows. Tresierra and Reyes (2018) aim to determine if the quality of national institutions condition the maturity of corporate debt, by exploiting a sample of 116 nonfinancial companies from Peru and Brazil. The authors show that a stable, democratic, transparent and effective social, legal and economic framework fosters confidence among financial actors, which in turn promotes long-term maturity obligations (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corruption is considered to be one of the major factors in deteriorating institutional quality of a country, and is also reported to have a significant negative relationship with a wide range of factors impacting small business growth (Krasniqi & Mustafa, 2016). In addition, prior studies further provide evidence on the relationship of corruption control on corporate disclosure, environmental regulations and economic development (Branco & Matos, 2016 Tresierra & Reyes, 2018). Thus, the current study aims to test the moderating effect of corruption control in the context of CSDC, using the following hypothesis;…”
Section: Hypothesis Developmentmentioning
confidence: 97%
“…Krasniqi & Mustafa (2016) used a questionnaire survey of 1,606 of Kosovar entrepreneurs, which empirically showed corruption to be an institutional quality variable that had significant influence on firm growth. More specifically, institutional quality affects the maturity of long-term debt, as was made evident by Tresierra & Reyes (2018) in a study of companies in both Peru and Brazil, which aimed at determining the extent to which national institutions condition the time horizon of debt maturity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For investors, these aspects lessen information asymmetry and systemic risk (Roe and Siegel, 2011). Several empirical studies, for instance, Kirch and Terra (2012), Tresierra and Reyes (2018) have found that institutional and financial development is an explicit link that facilitates the leverage by businesses. Additionally, ID may make it easier for businesses to obtain high level of debt on soft terms.…”
Section: Role Of Institutional Environmentmentioning
confidence: 99%